Coastal Community Empowerment Strategy through PT. Antam (Persero) Tbk UBPN Southeast Sulawesi’s CSR Program - Nur Azisyah Mukmin; Krisdyatmiko (CV. Literasi Indonesia, 2021)
This article attempts to analyze the coastal community empowerment strategy of PT. Antam (Persero) Tbk UBPN Sultra’s CSR program. A company which engages in the mining industry should be aware of the impact caused by its activity. 53% of people living in coastal areas, especially for fisherman communities seen their icome decreased. This research used qualitative descriptive approach to examine the company, local government, yayasanbahari, and coastal communities beneficiaries as its unit analysis while also using data collection techniques such as interviews, observation, and documentation to filter the appropriate data. The sustainable economy-based coastal community empowerment program has been carried out since 2017 in 3 (three) villages in Pomalaa District, Kolaka Regency, Southeast Sulawesi. The findings of this research are: a) there is social jealousy between groups of fisherman due to difference in ethnical identities of Bugis, Bajo, and Makassar tribes. This conflict is known as primordial conflict and can be reduced by the creation of trust via interaction between YayasanBahari and coastal communities; b) there is class conflict between the boss and labor fisherman. The interaction between the two is known as the patron-client relationship that has lasted for a long time and has prevent the coastal communities to become self-sustaining.